Partnership industrial relations of the retail sector and their relationship with trade unions in Malaysia - Chow, Amanda Joan (2019)
In this exploratory paper, we examine the views of retail workers, enterprise trade unions and national and regional trade union organizations on the role of partnership industrial relations in the retail sector of Malaysia, as well as the relevance of trade unions within this context through reference to a focused group interview. The practice of social dialogues as a method of communication in fostering positive industrial relations with employees have been practiced and implemented by regional, local and enterprise trade union and have indicated that employees and stakeholders were able to communicate effectively and achieve mutual understanding. Our findings yield that the practice of social dialogue in maintaining positive industrial relations has added value in sustainable long term industrial relations which benefits employers and stakeholders, which resulted in mutual respect, trust and sharing a common objective and vision as long as there are consensus building and involvement involved.